2014
DOI: 10.1080/24748668.2014.11868699
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between starting and finishing position in World Cup BMX racing

Abstract: .372, P <0.01.) for both male and female riders respectively. In conclusion, a strong correlation exists between riders position 8-10 s into a race. Therefore, focusing on a riders' ability to gain placings at the start of a race will have an effect on their finish line position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
(24 reference statements)
1
8
0
Order By: Relevance
“…One of the observations in their study was that the rate of force applied to the pedals was crucial as it had a direct effect on the start phase of a BMX race. The importance of the start of a BMX race on the overall race outcome was noted by Rylands and Roberts (2014). The authors analysed four UCI world cup events in 2012 using data from 348 riders across 175 elite BMX races.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the observations in their study was that the rate of force applied to the pedals was crucial as it had a direct effect on the start phase of a BMX race. The importance of the start of a BMX race on the overall race outcome was noted by Rylands and Roberts (2014). The authors analysed four UCI world cup events in 2012 using data from 348 riders across 175 elite BMX races.…”
Section: Discussionmentioning
confidence: 99%
“…The start of a Bicycle Motocross (BMX) race is a crucial aspect of performance, as it has been shown to have a direct correlation to a rider's final finishing position (Rylands & Roberts, 2014). There are a number of reported physiological considerations that contribute towards an optimum start, including peak power, rate of force produced and torque (Rylands, Roberts, Hurst & Bentley, 2015b;Bertucci & Hourde, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This gives riders a distinct advantage to best navigate the upcoming obstacles and contribute with a faster finish time (Cowell et al, 2012b). To gain the front position, BMX riders attempt to apply a maximum power effort using the leverage and strength of their upper and lower body (Herman et al, 2009;Mateo et al, 2011;Rylands et al, 2014). Factors that could affect power output such as gear ratio (Rylands et al, 2017b), optimal cadence (Rylands et al, 2017c), and the maximal torque and cadence relationship (Debraux et al, 2013;Gardner et al, 2007) have also been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…BMX Race is a sprint discipline with a race time between 30 to 40 s and a track of approximately 400 m. Because of the difficulties to overtake an opponent during the race, the start and the first straight line are crucial and have been shown to be directly correlated with rider's final position (Rylands and Roberts, 2014). The start of the race includes 2.5-3 pedal strokes and race analysis has revealed that riders achieve to be at the end of the bottom ramp at an average speed of 15.2 ± 0.4 m.s À1 within 2.47 ± 0.04 s (Gross et al, 2017).…”
Section: Introductionmentioning
confidence: 99%